Green Manufacturing for a Green Environment from Manufacturing Sector in Guangdong Province: Mediating Role of Sustainable Operations and Operational Transparency - Zulkaif Ahmed Saqib; Gang Xu; Qin Luo (Applied Sciences)
This work investigates the manufacturing operations of focal firms to manage the enhancement of environmental sustainability (EnS). To achieve this, indirect and direct effects of operational transparency (OPT) and sustainable operations (SUP) between environmental business practices (EBPr) and EnS are proposed. By leveraging the resource-based view theory, this study seeks to clarify how integrating transparency and sustainable operations can enhance a firm’s ability to manage environmental challenges effectively. Aligning environmental business practices with sustainable operations and transparency concepts appears to be an appropriate choice for environmental sustainability. A well-designed questionnaire was formed and used to collect the observations from 1214 focal firms. FsQCA and SEM approaches are employed to analyze one of the research questions of operations management: How do OPT and SUP mediate the effects of EBPr on the environmental sustainability of a firm? The final results clarify that the indirect effects of OPT and SUP significantly completely exist and are positive. The findings describe that firms with operational transparency and sustainability perform well in resolving operational and sustainable issues.